Cognitive Slowing, Dysfunction in Verbal Working Memory, Divided Attention and Response Inhibition in Post COVID-19 Condition in Young Adults - Johanna Takács; Darina Deák; Beáta Seregély; Akos Koller (Life)
After COVID-19 infection, about 30% of people have clinically persisting symptoms, characterized as Post COVID-19 Condition (PCC). One of the most reported symptoms in PCC is cognitive dysfunction, yet there are only a few studies investigating long-term effects on different domains of cognitive function. A total of 107 young adults, university students aged 18–34 years, participated. In total, 68.2% had contracted SARS-CoV-2; 21.9% showed PCC. Three groups were compared: no-C19 (COVID-19-negative controls), C19 (COVID-19-recovered without PCC) and PCC. Attention and executive function were measured with the Vienna Test System (Schuhfried®, Mödling, Austria). In verbal working memory, the PCC group had a significantly lower performance with a moderate effect. The rate of below-average performance was higher in PCC (56.2%) compared to no-C19 (20.6%) and C19 (15.8%). In divided attention and response inhibition, PCC also showed lower performance, 62.5% and 37.5%, respectively, than no-C19 and C19. The co-occurrence of decreased cognitive functions was pronounced in PCC. The present study revealed significant long-lasting cognitive dysfunction in PCC in young adults, two years after COVID-19 infection. Verbal working memory was significantly impaired, and a lower performance was found in divided attention and response inhibition. In addition, there was an increased reaction time in most cognitive tasks, demonstrating cognitive slowing in young people with PCC.